(untitled) (Gestão & Regionalidade, 2023)
The National Student Assistance Policy has contributed to the academic development of students at federal educational institutions. However, like other public bodies, these institutions were faced with the challenge of providing services efficiently to citizens. The article aims to analyze failures in the clinical care process of the Dental Service offered by the student assistance segment to students at a federal educational institution. Due to its complementary nature, the FTA and FMEA techniques were used to analyze the failures identified from process models created through the BPMN techniques, which recorded the sequence of activities, and DMN, which recorded the logic that guides decisions, the which influence the behavior of the process. The results of this application were the actions proposed to improve the selected process and a method aimed at improving business processes through failure analysis.